Genetic implications of new Sr and Nd isotopic data of the intrusive rocks from the Laramide Arc in Northern Sonora, Mexico. - Pérez-Segura, E.; González-Partida, E.; Roldán-Quintana, J. (Journal of Iberian Geology, 2013)
The Laramide Intrusive Arc constitutes a wide intrusive belt broadly parallel to the actual Sonora coastline. It was formed by the subduction of the Farallon Plate beneath the North-American Plate during the Late Cretaceous-Early Tertiary period. New isotopic data on rocks of this arc show initial 87Sr/86Sr and eNd isotopic values of 0.7066 to 0.7070 and -5 to -6, respectively, for two samples from Bacanora area; as well as 0.7074 to 0.7081 and -3 to -5.5 respectively, for five samples from Cananea, Mariquita and La Caridad areas. Isotopic ages were determined by U/Pb in zircons (95 Ma) and Ar/Ar in potassic feldspar (56 to 71 Ma) from a quartz monzonite porphyry, and by Ar/Ar in potassic feldspar (56 Ma) from another plutonic granodiorite, both from Bacanora. Initial 87Sr/86Sr and eNd values for samples reported in this study suggest that the Laramidic magmas had a large influence from the Proterozoic basement in northeastern Sonora. Four different isotopic zones are proposed for Sonora, according with Sr-Nd data of laramidic rocks and the substratum intruded.